Teaching of - and Research on English Pronunciation in Africa: A Multi-Model Approach (Global Journal of Human-Social Science, 2022)
This paper describes a novel way to conduct research on English pronunciation in Nigeria in particular and in Africa in general Thus far research in the continent consisted in identifying the characteristic features of the English used in each nation-state using one target model i e RP it can be said today that such research used a one-model approach In this study a multi-model approach is proposed The target model for research should not necessarily be RP but any varieties used in a given country s major business partner countries The central element in this multi-model approach is therefore international transactions This means that if a country like Ghana has India as its major trade partner country then the features of Indian English will have to be described in Ghanaian classrooms as well as research laboratories The present study focuses on Nigeria whose major business partner states are China India and the USA For this reason the features of the English spoken in these countries need to be highlighted in the pronunciation lectures and in research laboratories in Nigeria Familiarity of Nigerian citizens with these varieties is likely to enhance intelligibility as well as understanding in international interactions with the citizens of these countries
Keywords: english pronunciation; target model; research; teaching; chinese english; indian english; general american